School Management Strategies in Preventing Bullying - Rahmayanti, Firda; Faridah, Ida; Madum, Mohamad (Universitas Pahlawan Tuanku Tambusai, 2025)
Unfortunately, bullying is still a major issue in today's schools, negatively affecting both the emotional well-being and academic performance of students. Examining the methods used by school administrators to curb bullying in the classroom is the primary objective of this research. The research was conducted in a junior high school in [area name] using a qualitative approach. Data was gathered through in-depth interviews, observation, and documentation. The results of the study showed that bullying prevention efforts were carried out through three main strategies: (1) strict school policies against bullies, (2) strengthening student character through guidance and counseling services and religious activities, and (3) active involvement of parents and the community in supervision and education related to the impact of bullying. Also, the school uses digital media for advocacy and reporting. Based on these results, it's clear that a proactive, team-oriented approach to school safety can make a big difference for kids. The study's findings should hopefully inform the development of anti-bullying policies at other educational institutions.